Fermented Lentinus edodes extract containing α-glucan ameliorates concanavalin A-induced autoimmune hepatitis in mice - Xin Hu; Dan Cheng; Yingxia Zhang; Po Li; Xiaoping Wu; Junsheng Fu (Food Science and Human Wellness)
Autoimmune hepatitis (AIH) is a chronic inflammatory liver disease that threatens human health worldwide. The aim of this study was to detect the protective effect of a fermented Lentinus edodes extract containing α-glucan (FLA), in a concanavalin A (ConA)-induced AIH mouse model and to determine the underlying liver-protective mechanism. The results showed that compared with the model group, the level of proinflammatory cytokines in serum of FLA pretreated mice was significantly decreased, and the degree of inflammatory cell infiltration in liver, thymus and spleen was significantly reduced. Quantitative polymerase chain reaction, immunohistochemistry, and Western blotting showed that FLA pre-treatment inhibited the ConA-induced apoptosis of hepatocytes by down-regulating the expression of BAX and up-regulating the expression of BCL-2. Further research found that FLA may improve liver injury in mice by activating NRF2 signaling pathway and inhibiting TRAF6/NF-κB signaling pathway. Thus, FLA may improve liver injury in mice by shifting gut microbial composition to reduce the release of inflammatory cytokines in the serum and prevent the necrosis of hepatocytes. Up-regulation of NRF2 signaling pathway, down-regulation of TRAF6/NF-κB signaling pathway, and an increase in the relative abundance of Lactobacillus_johnsonii and Ligilactobacillus_murinus play a protective role in liver.